Editorial: establishing a joint approach to a common problem for gastroenterologists. Issue 2 (26th December 2019) - Luber, Raphael P.; Irving, Peter M.
Abstract : LINKED CONTENT This article is linked to Varkas paper. To view this article, visit https://doi.org/10.1111/apt.15519 .